2012
DOI: 10.1007/s00404-012-2425-0
|View full text |Cite
|
Sign up to set email alerts
|

A macrophage activation marker chitotriosidase in women with PCOS: does low-grade chronic inflammation in PCOS relate to PCOS itself or obesity?

Abstract: ChT activity elevates in PCOS independent of obesity. Our findings support the concept of PCOS is a state of low-grade chronic inflammation where the macrophages could play the major role. Hyperandrogenism might also be related to this inflammatory state and can be a subject of further trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 39 publications
1
27
0
Order By: Relevance
“…We firstly clarified that TGF-β and TNF-α induce PAI-1 mRNA expression and activity. PCOS is described as a low-grade chronic inflammatory state mainly triggered by an increase in activated macrophage infiltration in visceral fat 19 . It has also been reported that aberrant expression of TGF-β and TNF-α is related to PCOS, and macrophages are known to primarily secrete these cytokines 17, 18, 20, 21 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We firstly clarified that TGF-β and TNF-α induce PAI-1 mRNA expression and activity. PCOS is described as a low-grade chronic inflammatory state mainly triggered by an increase in activated macrophage infiltration in visceral fat 19 . It has also been reported that aberrant expression of TGF-β and TNF-α is related to PCOS, and macrophages are known to primarily secrete these cytokines 17, 18, 20, 21 .…”
Section: Discussionmentioning
confidence: 99%
“…PCOS is described as a low-grade chronic inflammatory state mainly triggered by an increase in activated macrophage infiltration in visceral fat. 19 It has also been reported that aberrant expression of TGFβ and TNFα is related to PCOS, and macrophages are known to primarily secrete these cytokines. 17,18,20,21 In the present study, simultaneous addition of TGFβ and TNFα had a synergistic effect on PAI-1 mRNA expression and activity, which was completely suppressed by a combination of ALK-5 and p38 MAPK inhibitors.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, ChT is considered as a biomarker of macrophage activation [6]. Human ChT is associated with several infectious and inflammatory diseases [7][8].…”
Section: Introductionmentioning
confidence: 99%
“…This enzyme is mainly secreted from activated and differentiated macrophages, therefore, ChT is a marker of macrophage activation (9). Human ChT is associated with Gaucher’s disease, lysosomal storage disorders, sarcoidosis, Crimean Congo hemorrhagic fever, and beta-thalassemia (10111213).…”
Section: Introductionmentioning
confidence: 99%